2008
DOI: 10.1111/j.1600-6143.2007.02133.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Long-Term Renal Graft Survival due to CMV Prophylaxis with Oral Ganciclovir: Results of a Randomized Clinical Trial

Abstract: Oral ganciclovir prophylaxis and intravenous preemptive therapy are competitive approaches to prevent cytomegalovirus (CMV) disease after renal transplantation. This trial compared efficacy, safety and long-term graft outcome in 148 renal graft recipients randomized to ganciclovir prophylaxis (N = 74) or preemptive therapy (N = 74). Hierarchical testing revealed (i) patients with CMV infection had more severe periods of impaired graft function (creatinine clearance max−min 25.0 ± 14.2 mL/min vs. 18.1 ± 12.5 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
205
4
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(243 citation statements)
references
References 36 publications
18
205
4
7
Order By: Relevance
“…We found that eGFR was lower in both EOD and LOD patients than in patients without disease. This finding confirms the poorer prognosis associated with LOD but shows that EOD is also associated with more chronic allograft dysfunction than is seen in patients free of CMV disease, as has already been described by Kliem et al (32). Indeed, patients using a preemptive strategy (i.e.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We found that eGFR was lower in both EOD and LOD patients than in patients without disease. This finding confirms the poorer prognosis associated with LOD but shows that EOD is also associated with more chronic allograft dysfunction than is seen in patients free of CMV disease, as has already been described by Kliem et al (32). Indeed, patients using a preemptive strategy (i.e.…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, patients using a preemptive strategy (i.e. a marker of early disease) had lower graft survival than patients who received universal prophylaxis (32), but direct comparison between EOD and LOD was not done.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most studies have indicated that successful antiviral prophylaxis has a beneficial effect on long-term graft function (8). This suggests that viral replication is a component of risk, but the precise mechanisms underlying this effect are debated (9,11,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Important considerations are the indirect effects of CMV on transplant-related endpoints, such as rejection and long-term graft function, which are linked to CMV by circumstantial evidence. Some studies show an advantage of prophylaxis over preemption for these indirect effects [7], while others do not [8,9]. The major hurdles for the preemptive strategy are the logistics necessary not only to ensure timely assessment of biomarkers, but also to take appropriate and prompt action upon receipt of the result.…”
Section: Discussionmentioning
confidence: 99%